Enabling humans to hear the direction of sounds underwater - Experiments and preliminary results - Teong Beng Koay; Jolyn Tan; Soo Pieng Tan; Soon Keat Yeo; Tay, H.; Chitre, M.; Potter, J.R. (Oceans 2008, 2008)
Sound localization by the human auditory system is known to be ineffective underwater. In a research study at the Acoustic Research Laboratory, we introduce additional directional cues from ultra-sonic frequency components. This enables us to work with smaller wavelengths and build simple, small, directional receivers in order to introduce Inter-aural Temporal Differences (ITD) and Inter-aural Intensity Differences (IID) cues to the human subjects. Along with a real-time acoustic bandwidth compression algorithm, we are able to introduce a sense of direction into their hearing in water. The prototype system consists of a pair of directional receivers of less than 60 mm diameter that are spaced and angled in such a way that high frequency directional cues from 20 kHz-200 kHz are created in the audio hearing range, providing a sense of direction. Several experiments have been conducted in a small tank to study the performance of the system. The preliminary results are very promising. Independent tests on the directional receivers show that subjects are able to differentiate direction to within plusmn12 degree 95% of the time. The subjects claim that there was a clear sense of direction in their hearing tests. Results from swimming pool experiments indicate that subjects wearing the prototype system demonstrate capability in direction localization, although the sense of direction seems somewhat reduced compared to the independent tests on the directional receivers. This paper presents the experimental design, and preliminary analysis of the data.